Successful Percutaneous Retrieval of an Embolized Umbilical Venous Catheter Fragment Lodged in the Left Atrial Appendage: A Case Report - Shah, Subhash Chandra; Bajracharya, Amshu Shakya; Shakya, Urmila; Shrestha, Manish (Nepalese Heart Journal, 2026)
Background: Umbilical venous catheters (UVCs) are essential in neonatal intensive care but can rarely fracture and embolize, causing life-threatening complications. Management traditionally required surgery, but percutaneous retrieval offers a minimally invasive alternative. Case Presentation: We report a 16-day-old preterm male neonate (33 + 4 weeks, 1990 g) with a fractured UVC fragment that migrated from the right atrium across a patent foramen ovale into the left atrial appendage. The initial retrieval attempt was aborted due to bradycardia; however, following stabilization, successful percutaneous retrieval was achieved via the right femoral vein approach using a Judkins guiding catheter and gooseneck snare. Conclusion: Percutaneous retrieval of embolized UVC fragments is feasible and safe, even from unusual locations such as the left atrial appendage, and should be considered the preferred management option.